Subluminal group velocity and dispersion of laguerre-gauss beam in free space - Bareza, Nestor D. Jr (Institute of Physics, College of Science, University of the Philippines Diliman, 2016)
Physical light beams naturally have transverse structures that alter the wave vector to include non-axial components k. The presence of K makes the group velocity vg of physical light to be less than the speed limit c. Thus, physical light propagates with subluminal speed even in free space. This study is significantly important both in revisiting the fundamental nature of light propagation and in extensive application of LG beams.